Internet connectivity disruption in Bosnia and Herzegovina (Bosnia and Herzegovina) - Voidly (2026)
CRITICAL severity disruption detected in Bosnia and Herzegovina. Confidence: 67%. Data sourced from IODA.
Network Disruption Incident ID: BA-2026-0053
Keywords: internet disruption; BA; disruption; critical